Pembinaan Strategi Perencanaan Usaha UMKM Menuju Bisnis Digital dengan Metode Business Model Canvas - Yudhi Prasetiyo; Sila Ninin Wisnantiasri; Nindya Farah Dwi Puspitasari; Novta Winkey Pradana; Shufia Zuhroh; Nadhira Hardiana; Krist Setyo Yulianto (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
This community service aims to increase the capacity of MSMEs in Situ Udik Village in designing a digital-based business framework using the Business Model Canvas (BMC) approach. Through training and mentoring, participants are guided to develop a business model that includes nine main elements, from customer segments to cost structures. The results of the activity showed that most participants succeeded in developing a more systematic business framework, recognizing business strengths and weaknesses, and formulating medium-term development strategies. In addition, participants began to integrate digital promotions through social media and design more effective distribution channels. Several MSMEs have also begun to utilize simple applications for financial recording. These findings indicate that BMC is effective as a tool for developing digital business models, encouraging MSMEs to be more adaptive and competitive in facing market changes and preparing sustainable business growth strategies.